2007
DOI: 10.2108/zsj.24.147
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of Vacuolar Proton-Pumping ATPase Subunits in the Follicular Epithelium of the Bullfrog Endolymphatic Sac

Abstract: In an investigation aimed at clarifying the mechanism of crystal dissolution of the calcium carbonate lattice in otoconia (the mineral particles embedded in the otolithic membrane) of the endolymphatic sac (ELS) of the bullfrog, cDNAs encoding the A-and E-subunits of bullfrog vacuolar protonpumping ATPase (V-ATPase) were cloned and sequenced. The cDNA of the A-subunit consisted of an 11-bp 5'-untranslated region (UTR), a 1,854-bp open reading frame (ORF) encoding a protein comprising 617 amino acids with a cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
4
4
0
Order By: Relevance
“…The high signal-to-noise ratio, along with specific organellar markers allowed us to clearly discern V-ATPase-positive organelles, primarily endo/lysosomes and the trans -Golgi. This labeling was in sharp contrast to the staining we obtained using a commercially available antibody to the A subunit and the conditions for its use described in the literature (Ramirez et al, 2019), which yielded results similar to those reported by others using other available antibodies (Yajima et al, 2007; McGuire et al, 2019; Michel et al, 2013). V-ATPase complexes have been shown to interact with several accessory proteins involved in endocytic sorting and signaling (Merkulova et al, 2015; Maxson and Grinstein, 2014; Marshansky et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The high signal-to-noise ratio, along with specific organellar markers allowed us to clearly discern V-ATPase-positive organelles, primarily endo/lysosomes and the trans -Golgi. This labeling was in sharp contrast to the staining we obtained using a commercially available antibody to the A subunit and the conditions for its use described in the literature (Ramirez et al, 2019), which yielded results similar to those reported by others using other available antibodies (Yajima et al, 2007; McGuire et al, 2019; Michel et al, 2013). V-ATPase complexes have been shown to interact with several accessory proteins involved in endocytic sorting and signaling (Merkulova et al, 2015; Maxson and Grinstein, 2014; Marshansky et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…When tested in HeLa cells (Figs. 4G and H), this antibody yielded a diffuse punctate pattern reminiscent of that reported by Ramirez et al (2019) for tumour cells and elsewhere for a variety of other cells stained with other A subunit antibodies (Yajima et al, 2007;McGuire et al, 2019;Michel et al, 2013). However, its co-localization with acidic compartments was poor: the Manders' coefficient of the antibody with LAMP1 was M = 0.08 (compared to an M = 0.79 with SidK-AL568), while that with anti-TGN46, the trans-Golgi marker used, was M = 0.05 (compared to an M = 0.81 with SidK-AL568).…”
Section: Localization Of the V-atpase In Mammalian Cells Using Sidk-al568supporting
confidence: 69%
“…Antibodies were raised in a rabbit or guinea pig immunized with the ST-200 peptide coupled to keyhole limpet hemocyanin, as described previously (43). Rabbit or guinea pig anti-peptide antibodies were previously generated for X. laevis AQP5 homologue, AQP-x5(b) (26), and X. laevis AQP3, AQP-x3BL (30), bullfrog vacuolar H ϩ -ATPase (V-ATPase) E-subunit (46).…”
Section: Methodsmentioning
confidence: 99%
“…Double-immunofluorescence staining was carried out to elucidate the detailed distribution of AQPs in the acinar cells of the small granular gland. Staining against AQP-xt5a and V-ATPase E-subunit, a marker molecule for mitochondrion-rich cells (46), depicted AQP-xt5a in secretory cells of the small granular gland of dehydrated frogs, but not in the mitochondrion-rich cells (Fig. 9A).…”
Section: Characterization Of Aqp-xt5 and Synteny Analysismentioning
confidence: 99%
“…The antibody was raised in a rabbit immunized with the ST-203 peptide coupled to keyhole limpet hemocyanin (Pierce, Rockford, Ill., USA), as described by Tanaka and Kurosumi (1992). Antibodies against Xenopus AQP-x5 (ST-156; Kubota et al 2006) homologous to mammalian AQP5, against the bullfrog vacuolar H + -ATPase (V-ATPase) E-subunit (ST-173; Yajima et al 2007) for identifying mitochondria-rich (MR) cells, and against Hyla AQP-h2 (ST-140; were generated in guinea pigs and characterized as described previously.…”
Section: Antibodiesmentioning
confidence: 99%